2011
DOI: 10.1111/j.1365-2052.2011.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in bovine transferrin receptor 2 (TFR2) and solute carrier family 40 (iron‐regulated transporter), member 1 (SLC40A1) genes and their association with beef iron content

Abstract: SummaryBeef is considered to be an excellent source of dietary iron. However, little is known about the genetic control of beef iron content. We hypothesized that genetic polymorphisms in transferrin receptor 2 (TFR2) and solute carrier family 40 (iron‐regulated transporter), member 1 (SLC40A1) could influence skeletal muscle iron content. The objective of this study was to use Angus cattle to identify single‐nucleotide polymorphisms (SNPs) in the exons and flanking regions of the bovine TFR2 and SLC40A1 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Liver zinc concentration, however, was different between Limousin and Pinzgauer cattle, but not among the other breeds. While we did not identify breed effects on these five mineral concentrations within LT, it is possible for mineral concentrations to be influenced by genetics which vary within breed (Casas et al, 2014;Duan et al, 2011;. In a large study in lambs, Pannier et al (2014) identified significant effects of sire type on iron (P b 0.01) and zinc (P b 0.05) concentrations in LT.…”
Section: Breed Effect On Mineral Concentrationmentioning
confidence: 72%
See 1 more Smart Citation
“…Liver zinc concentration, however, was different between Limousin and Pinzgauer cattle, but not among the other breeds. While we did not identify breed effects on these five mineral concentrations within LT, it is possible for mineral concentrations to be influenced by genetics which vary within breed (Casas et al, 2014;Duan et al, 2011;. In a large study in lambs, Pannier et al (2014) identified significant effects of sire type on iron (P b 0.01) and zinc (P b 0.05) concentrations in LT.…”
Section: Breed Effect On Mineral Concentrationmentioning
confidence: 72%
“…Beef mineral concentrations vary among individuals and are affected by various physiological, environmental, and within breed additive genetic factors (Doyle, 1980;Duan et al, 2011;Zarkadas et al, 1987). Few studies have evaluated mineral concentrations across several sire and dam breeds of cattle.…”
Section: Introductionmentioning
confidence: 99%
“…SLC40A1 encodes ferroportin which is an iron transporter involved in iron export from cell, and it is essential for iron homeostasis. Moreover, Duan et al found that the polymorphisms of this gene as well as TRF2 (transferrin receptor 2) were significantly associated with beef iron concentration [16]. It is possible that the polymorphisms of SLC40A1 have an effect on iron homeostasis of bovine breast cells, which leads to a potential relationship with milk yield.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the large size of this CSS, selective sweeps that originally did not include the GDF -8 gene have been incorporated under the CSS-32 label; these include two sweeps described in a Piedmontese vs. Italian Brown comparison (Pintus et al, 2014 ) 6.717–9.760 Mb, including the SLC40A1 (solute carrier family 40, member 1), COL5A2 (collagen, type V, alpha 2), COL3A1 (collagen, type III, alpha 1), CALCRL (calcitonin receptor-like) and ITGAV (integrin, alpha V) genes, and a Fleckvieh selective sweep located in a gene-desert region. Polymorphisms in the SLC40A1 gene have been related to beef iron content (Duan et al, 2012 ).…”
Section: Plausible Candidate Genes Underlying Css Regionsmentioning
confidence: 99%